(untitled) (Baghdad Science Journal, 2021)
There are many animal models for polycystic ovary (PCO); using exogenous testosterone enanthate is one of the methods of induction of these models. However, induction of insulin resistance should also be studied in the modeling technics. Therefore, the present study aims to investigate the expression of insulin receptor substrate (Irs)-2 mRNA in the liver tissue of rat PCO model. Nineteen Wistar rats were divided into three groups; (1) PCO modeling group (N =7) received daily 1.0 mg/100g testosterone enanthate solved in olive oil along with free access dextrose water 5%, (2) vehicle group (N =6), which handled like the PCO group, but did not receive testosterone enanthate, (3) control group (N =6) with standard care. All the animals were administered via intra-peritoneal injection for 14 days. Expression of Irs-2 mRNA was studied with real-time PCR and fold changes (FC) were reported. The average of expression in the control group was considered as the calibrator. About 13.4% expression reduction was found in the PCO group (FC =0.874, P-value =0.043). No significant reduction was found in the vehicle group (FC =0.951, P-value =0.076). However, analysis of variance did not show a significant difference between all the groups of study (P-value =0.085). The present model of PCO might induce insulin resistance at liver level with a low effect size via reduction in the mRNA expression of Irs-2. Study of the involved genes and molecules in other tissues of PCO animal models is suggested.